2011
DOI: 10.2147/ijn.s25825
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, appraisal, and transdermal permeation of sildenafil citrate-loaded nanostructured lipid carriers versus solid lipid nanoparticles

Abstract: Although sildenafil citrate (SC) is used extensively for erectile dysfunction, oral delivery of SC encounters many obstacles. Furthermore, the physicochemical characteristics of this amphoteric drug are challenging for delivery system formulation and transdermal permeation. This article concerns the assessment of the potential of nanomedicine for improving SC delivery and transdermal permeation. SC-loaded nanostructured lipid carriers (NLCs) and solid lipid nanoparticles (SLNs) were fabricated using a modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…20 The samples were then analyzed by HPLC. Control experiments were performed in the same way using the same proportions of gentiopicrin and oleanolic acid as in the GONLCs to investigate drug release behavior.…”
Section: In Vitro Releasementioning
confidence: 99%
“…20 The samples were then analyzed by HPLC. Control experiments were performed in the same way using the same proportions of gentiopicrin and oleanolic acid as in the GONLCs to investigate drug release behavior.…”
Section: In Vitro Releasementioning
confidence: 99%
“…Size stability results revealed that both SLNs and NLCs kept their particle size during 6 months of storage, demonstrating the good physical stability of the particles. 33 Souto et al prepared clotrimazole-loaded SLN with Dynasan® 116 as the solid lipid and NLC with the same lipid accompanied by 30% Miglyol® 812 as the oil. Their results showed no significant difference in size between NLC and SLN produced with the same total lipid and surfactant composition.…”
Section: Introductionmentioning
confidence: 99%
“…6,[14][15][16][17][18][19][20][21][22] Lipidbased liquid crystalline nanoparticles (LCN) have recently captured the obvious interest of pharmaceutical research to enhance the bioavailability of lipophilic drugs. 23 LCN enjoy characteristics of biocompatibility, bioadhesivity, and biodegradability offering various advantages for brain delivery.…”
Section: Introductionmentioning
confidence: 99%